Thickness dependence of the structural and electrical properties of copper films deposited by dc magnetron sputtering technique - CHAN, K; TOU, T; TEO, B (2006)
This paper addresses the influences of film thickness on structural and electrical properties of dc magnetron sputter-deposited copper (Cu) films on p-type silicon. Cu films with thicknesses of 130-1050 nm were deposited from Cu target at sputtering power of 125 W in argon ambient gas pressure of 3.6 mTorr at room temperature. The electrical and structural properties of the Cu films were investigated by four-point probe, atomic force microscopy (AFM) as well as X-ray diffraction (XRD). Results from our experiment show that the grain grows with increasing film thickness, along with enhanced film crystallinity. The root mean square (RMS) roughness as well as the lateral feature size increase with the Cu film thickness, which is associated with the increase in the grain size. On the other hand, the Cu film resistivity decreases to less than 5 mu Omega-cm for 500 nm thick film, and further increase in the film thickness has no significant effects on the film resistivity. Possible mechanisms of film thickness dependent microstructure formation of these Cu films are discussed in the paper, which explain the interrelationship of grain growth and film resistivity with increasing Cu film thickness. (C) 2005 Elsevier Ltd. All rights reserved.